Perlindungan Hukum terhadap Pemegang Hak Cipta Sinematografi terkait Tindakan Spoiler Film dan Serial pada Aplikasi Tiktok (Hasanuddin Civil and Bussiness Law Review, 2024)
Cinematographic works are creations in the form of moving images, including documentaries, advertising films, reports, or feature films made with scenarios and cartoon films. The provisions of Article 40 Paragraph (1) Letter (m) of Law Number 28 of 2014 Concerning Copyright or commonly referred to as UUHC is a form of recognition of cinematographic copyrighted works as creative thoughts that must be protected, because their circulation is still found freely without the permission of the creator and/or copyright holders on the TikTok application due to spoiler actions. Spoiler actions can be categorized as distribution and publication of works which are part of the economic rights of the creator and/or copyright holders. The rise of this action attracts attention of several parties, especially Starvision Plus and Finisia Production as the production team for several films and series in Indonesia. This study uses empirical legal research method. This sample was taken using a purposive sampling method with a total sample of 13 people. Obtained from primary and secondary data collected thru interviews and literature study, then analyzed in a descriptive and qualitative approach. The resulst of this study are: (1)TikTok’s efforts to deal with these violations include paying attention to the interests of its users, blocking access to content, and closing offending accounts. (2) Efforts taken by copyright holders include alerting pirates, reporting them as the official owners of films and series to the relevant platforms, cooperating with producer associations and other film business actors, as well as socializing regulations related to copyright protections.
Keywords: Cinematography Copyright; Spoilers; TikTok